High temperature quantum tunnelling of magnetization and thousand kelvin anisotropy barrier in a Dy2 single-molecule magnet. Issue 3 (16th December 2020) - Wu, Haipeng; Li, Min; Xia, Zhengqiang; Montigaud, Vincent; Cador, Olivier; Le Guennic, Boris; Ke, Hongshan; Wang, Wenyuan; Xie, Gang; Chen, Sanping; Gao, Shengli
Abstract : The control of the crystal field environment within the cis / trans stereoisomers allowed the observation of a significantly enhanced anisotropy barrier to 1300 K and magnetic hysteresis opened up to 16 K. Abstract : We report here a dinuclear Dy III iodine-bridged single-molecule magnet self-assembled by cis / trans coordination chemistry that displays a large anisotropy barrier of ca. 1300 K and a hysteresis opening temperature of 16 K. High temperature quantum tunnelling of magnetization is observed up to 56 K in zero-field and explained by the combination of the large anisotropy barrier and the local transverse field at the trans site. The results provide a model for thorough understanding of the effect of electronic structure on the magnetic behavior of lanthanide complexes.